2002
DOI: 10.1073/pnas.072660299
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting levels of selection in the accumulation of mitochondrial defects in Saccharomyces cerevisiae

Abstract: The somatic accumulation of defective mitochondria causes human degenerative syndromes, senescence in fungi, and male sterility in plants. These diverse phenomena may result from conflicts between natural selection at different levels of organization. Such conflicts are fundamental to the evolution of cooperating groups, from cells to populations. We present a model in which defective mitochondrial genomes accumulate because of a within-cell replication advantage when among-cell selection for efficient respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
89
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(96 citation statements)
references
References 36 publications
4
89
0
Order By: Relevance
“…Implicit in the term ''symbiont'' is the mutual beneficial association between the two interacting partners. However, to a great extent, the functional mitochondrial genomes are altruistic; they contribute to the respiration machinery of the cell at the expense of their own rate of replication (1). Further, mitochondrial genomes have, to some extent, undergone a streamlining process or ''reductive evolution'' (2), leading to a marked loss of coding capacity compared with that of their closest eubacterial relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Implicit in the term ''symbiont'' is the mutual beneficial association between the two interacting partners. However, to a great extent, the functional mitochondrial genomes are altruistic; they contribute to the respiration machinery of the cell at the expense of their own rate of replication (1). Further, mitochondrial genomes have, to some extent, undergone a streamlining process or ''reductive evolution'' (2), leading to a marked loss of coding capacity compared with that of their closest eubacterial relatives.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is substantial circumstantial evidence for the significance of high relatedness among the mtDNA within an individual, direct evidence supporting this hypothesis is scarce [4,18]. In this paper, we experimentally study the significance of high relatedness among the mtDNAs within an individual for selection among individuals against dysfunctional selfish mtDNA variants.…”
Section: Introductionmentioning
confidence: 99%
“…by a replication benefit) can increase in frequency even if these decrease individual-level fitness [3]. Such selfish mitochondrial mutants are well known from yeast [4]. With a frequency of about 1%, yeast cells mutate to form mini colonies containing far fewer cells than the wild-type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical and empirical studies have indicated that multilevel selection in structured populations may be important in explaining diverse biological phenomena, including the evolution of social behavior (FRANK 1998;HAMILTON 1996;HAMILTON 1964;WILSON 1997), intragenomic conflict (HURST et al 1996INGVARSSON and TAYLOR 2002;TAYLOR et al 2002), reduced pathogen virulence (KERR et al 2006;, sex ratio evolution (MCCAULEY and TAYLOR 1997;OLSON et al 2005), and the origins of multi-cellularity (MICHOD 1997;MICHOD 1999;SZATHMARY and SMITH 1995) . Recent conceptions of multilevel selection theory have broadened its applicability by recognizing that the effects of group membership on individual fitness, so-called contextual effects (HEISLER and DAMUTH 1987), is a group-level effect that can be distinguished from a group's potential to give rise to other groups (HEISLER and DAMUTH 1987;OKASHA 2004; so-called multilevel selection 1 (MS1) and MS2, respectively) .…”
Section: Introductionmentioning
confidence: 99%